Athletic satisfaction and passion of elite handball brazilian women athletes (Research, Society and Development, 2020)
This study aimed to analyze the athletic satisfaction and passion of elite handball Brazilian athletes. Subjects were 88 women handball athletes, participants of Brazilian Woman Handball Championship - Adult category (2016). The instruments were an identification form, Athletic Satisfaction Questionnaire and Passion Scale. Data were analyzed with Kolmogorov Smirnov, U of Mann Whitney and Spearman correlation coefficient (p